Classroom Nutrition Education Combined With Fruit and Vegetable Taste Testing Improves Children's Dietary Intake. (February 2017) - Gold, Abby; Larson, Mary; Tucker, Jared; Strang, Michelle
ABSTRACT: BACKGROUND: We tested the effectiveness of the Go Wild With Fruits and Veggies! (GWWFV) Extension curriculum on increasing fruit and vegetable (FV) intake of third graders. METHODS: An intervention study was used testing self‐reported FV intake pre/post GWWFV. Recruited schools were randomized to control (12 schools, N = 369, third grade children) or intervention (14 schools, N = 378, third grade children). Measures included items from a validated FV food frequency survey. Access to the federal Fresh Fruit and Vegetable Snack Program (FFVSP), and taste testing within GWWFV were also measured. Between‐group differences in FV intake were evaluated using 1‐way ANOVA for unadjusted models and 1‐way ANCOVA for baseline adjusted models. The Tukey‐Kramer test was employed for post hoc comparisons. RESULTS: Students with access to the FFVSP consumed more fruits (p < .01) and vegetables (p < .0001). Students who participated in the FFVSP and GWWFV with taste testing consumed more fruits and vegetables (p < .05) compared with students who participated in the FFVSP and GWWFV without taste testing, along with the control group. CONCLUSIONS: The FFVSP and GWWFV with taste testing demonstrated a positive influence on FV intake in third grade children. Leveraging environmental approaches with interactive learning experiences create desired outcomes.